FEM-based virtual manufacturing for deformation analysis of coupled welding-forming process / Keval Priapratama Prajadhiana ... [et al.] - Prajadhiana, Keval Priapratama; Manurung, Yupiter H.P; P Ishak, Dendi; Marcel, Graf; Birgit, Awiszus; Andre, Haelsig; Hui, Leng Choo (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
This research presents the development of Virtuall Manufacturing (VM) procedure using Finite Element Method (FEM) for analysing the final deformation behaviour of coupled welding-forming process. The chained process simulation was executed by using FEM-based VM software Simufact.Welding and Simufact.Forming. The initial GMAW welding process is executed prior forming process and was modelled and simulated for of 2mm thickness butt joint made of DC04 low carbon steel material prior to forming process. In welding simulation, the weld bead is modelled using a simplified bead geometry without reinforcement and the heat source model is based on Goldak's double ellipsoid model. The result of welding simulation is transferred to Simufact.Forming under the consideration of additive isotropic hardening plasticity model based on von-mises yield criteria. In this VM procedure, temperature distribution for calibration purpose, material history transfer, damage criteria are put into consideration. As final outcome, it can be concluded that a proper VM procedure should be implemented to obtain desired results for industrial application. The result between VM simulation and experiment shows a good agreement in term of error percentage which falls within the range of 4.35%-33.1% in total deformation result.